1985
DOI: 10.1093/nar/13.2.389
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence recognised by the Escherichia coli D type I restriction and modification enzyme

Abstract: A type I restriction endonuclease from a new isolate of Escherichia coli (E. coli E166) has been purified and characterised. The enzyme, EcoD, has a recognition sequence similar in overall structure to the previously determined type I enzyme sequences, an exception being that it is degenerate. The sequence is 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…3C). In fact, B and D differ only at position 18 and the carboxyl terminus, although the tetranucleotide elements of their target sequences are very different (7,8): TGCT for B and GTCY for D. Gough and Murray (4) concluded that there was insufficient variability here for the different specificities of interaction. The inclusion of the sequences for the Salmonella polypeptides increases the diversity, but three of the differences are common to both Salmonella specificities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). In fact, B and D differ only at position 18 and the carboxyl terminus, although the tetranucleotide elements of their target sequences are very different (7,8): TGCT for B and GTCY for D. Gough and Murray (4) concluded that there was insufficient variability here for the different specificities of interaction. The inclusion of the sequences for the Salmonella polypeptides increases the diversity, but three of the differences are common to both Salmonella specificities.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA sequences recognized by type I restriction enzymes comprise specific trinucleotide and tetranucleotide (or pentanucleotide) segments separated by a spacer of defined length but of nonspecific sequence (7)(8)(9). One interpretation of the heteroduplex analyses correlates the two variable regions of the hsdS gene, and hence of the S polypeptide, with the two specific segments of the DNA target sequence (4).…”
mentioning
confidence: 99%
“…DNAs from laboratory and natural isolates of E. coli were screened, as well as a small sample of DNAs of other enteric bacteria. Related specificity systems were detected, some of which have been described elsewhere (19,23,29), and both the K and A families were represented in more than one genus. Nevertheless, as judged by our failure to detect homologous sequences, most E. coli strains lacked either Kor A-related hsd genes.…”
mentioning
confidence: 82%
“…The sequences of recognition sites are asymmetric but not palindromic. Examples include 5′-AACN 6 GTGC-3′ and 5′-GCACN 6 GTT-3′ for EcoKI, 5′-TGAN 8 TGCT-3′ and 5′-AG-CAN 8 TCA-3′ for EcoBI, and 5′-TTAN 7 GTCY-3′ and 5′-RGACN 7 TAA-3′ for EcoDI (methylated adenine is underlined; R: A/G, Y: C/T, N: A/C/G/T) [29,30].…”
Section: Type I Rm Systemsmentioning
confidence: 99%
“…Recent epigenetic studies have developed many methods to analyze DNA methylation [29,30,[69][70][71][72][73][74][75][76]. Although most of these studies aimed to analyze 5-methylation of cytosine at spe-cific sites, or differential DNA methylation in chromosomes, there are a few methods that exhaustively determine methylated consensus sites in chromosomes as follows.…”
Section: Methylation Site Analysismentioning
confidence: 99%